Perancangan Primer Oligonukleotida untuk Polimerisasi in Vitro Gen Sukrosa Sintase - Pieter Agustinus Riupassa (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2009)
The most important problems in using polymerase chain reaction (PCR) are the efficiency of energy, cost and time due to gene amplification. Oligonucleotide primer design of sucrose synthase gene was conducted as a model of preliminary experiment to amplify gene using PCR. In plant cells, this gene plays an important role in carbohydrate metabolism, a sucrose molecule break down into glucose. This design involved some computer software as bioinformatics tools. Five data sequences of legumes were downloaded from gene bank using accession number of AF030231, AJ311496, X92378, X69773, and D10266 belongs to soybean, pea, alnus bean, fava bean, and mung bean, respectively. After sequences alignment, some conservative regions were determined as the basis to construct forward and reverse primer candidates. Furthermore, the candidates were tested for compatibility. The results showed that the oligonucleotide primers can amplify sucrose synthase gene with ± 1462 bp fragment size using 5’-AACTTTgTgCTTgA-3’ and 5’-TCCTTTgACTCCTTC-3’ for forward and reverse primer, respectively. Even the PCR process weren’t applied, those primers might be universal primers to amplify sucrose synthase gene of legume plants.